Survival outcomes of population-wide colonoscopy screening: reanalysis of the NordICC data - Tomer Meirson; Gal Markel; Daniel A. Goldstein (BMC Gastroenterology)
Abstract Background Colonoscopy as a common screening practice to prevent colorectal cancer lacks strong evidence. NordICC, the first randomized trial of colonoscopy screening, reported no clear clinical benefit for colonoscopy in the intention-to-screen population with suggested benefit in the risk of colorectal incidence and cancer-specific mortality in the per-protocol analyses. However, although the study was designed to perform survival analysis, no survival outcomes were reported since the underlying assumption for hazard ratio was not valid. We aimed to assess whether colonoscopy screening is associated with improved survival outcomes compared with usual care. Methods We reconstructed patient-level data from the Kaplan-Meier estimator of the primary endpoints reported in NordICC for the intention-to-screen and adjusted per-protocol populations. The restricted-mean survival time difference (RMST-D) and restricted-mean time loss ratio (RMTL-R), which are robust alternatives to the hazard ratio without specific model assumptions, were calculated for colorectal cancer incidence and death. Results In this study, no significant difference in colorectal cancer incidence over 10 years was found in the intention-to-screen population (RMST-D: -0.68 days, 95% CI -3.9–2.6; RMTL-R: 1.04, 95% CI 0.88–1.22) or in the per-protocol analysis population (RMST-D: -2.9 days, 95% CI -6.5–0.67; RMTL-R: 1.15, 95% CI 0.97–1.35). In the intention-to-screen population, inviting individuals to colonoscopy did not improve colorectal-cancer death (RMST-D: -0.29 days, 95% CI -1.6–1.0; RMTL-R: 1.07, 95% CI 0.78–1.48). Over 10 years, in the per-protocol analysis, individuals who underwent colonoscopy survived an average of 1.1 more days free of colorectal cancer, but this difference was not statistically significant (RMST-D: 95% CI -0.13–2.3; RMTL-R: 0.72, 95% CI 0.49–1.07). Conclusions In this reanalysis of the NordICC data, no evidence of improvement in survival outcomes for participants invited to undergo colonoscopy compared to usual care was identified, even when assuming that all invited participants did undergo colonoscopy. Thus, our results do not support the use of colonoscopy as a population-wide screening test as a mean to decrease colorectal cancer incidence or death. Registry Not applicable.